The Role of Students in Guarding the Constitution and Building Awareness and Optimism of Legal Politics - Clinton Ody Folsen Ambarita; Rahul Ardian Fikri (International Journal of Law, Crime and Justice, 2024)
Students play professional and appropriate roles in society and education as intellectuals and value-added members of society. The purpose of this study is to identify the role of students in protecting the constitution and the role of students in building socio-political awareness and optimism. The research method used in this study is theoretical research, using conceptual methods and legal methods. In preparing this article, the author used Google Schoolar to put library resources online. The conclusion of this study is that upholding the Constitution is not only the task of the Constitutional Court or a few special individuals and institutions, but also of students. Therefore, students must not only play the role of defenders of the Constitution, but also integrate the character of young intellectuals. This oversight may be accomplished in a variety of ways, including through student submission of judicial reports. How important it is for students to work to build public trust in politics. One of the most serious problems for our country and nation today is the issue of public trust in politics.